Pemaknaan Khalayak terhadap Sikap Keterbukaan Diri Penyintas Kekerasan Seksual dalam Film Penyalin Cahaya (2021) - Nuraini Purnomo, Amelia; Bayu Widagdo, Muhammad; Yusriana, Amida (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Photocopier (2021) is a thriller genre film that addresses the issue of sexual violence and critiques the legal and social systems of Indonesian society. This research aims to uncover the audience's interpretation of the openness of sexual violence survivors as depicted in the film Photocopier (2021). This study employs Standpoint Theory, Muted Group Theory, and John Fiske's semiotics analysis method to identify preferred reading’s and Stuart Hall's reception analysis to fulfill the research objectives. Findings from interviews with five respondents, both male and female, with varying experiences related to sexual violence, reveal diverse interpretations of the openness of sexual violence survivors. Two non-survivors have differing dominant and negotiated interpretations, though they agree that the portrayal of sexual violence survivors in Photocopier (2021) mirrors reality. On the other hand, two sexual violence survivors and one close associate of a survivor hold opposing interpretations. They believe that the portrayal of open survivors in the film does not align with reality. Finally, all five respondents agree with the depiction of other elements, such as characterizations and the attitudes of perpetrators, the survivors' close associates, and authorities, and believe that these elements reflect reality.